IDEAL ROMANCE FORMULA IN THE MOVIE SCRIPT OF EMMA (2020) AND PERSUASION (2022): COMPARATIVE LITERATURE - Yasmin Rifdah Luthfiah; Hasbi Assiddiqi; Udayani Permanaludin (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
Romance movie scripts are one of the most popular types of popular literature. But most fans don't know that in a work of popular literature there is a formula that is quite important because it influences the plot of the story and helps the audience to understand more about the story. Examples of romance movie scripts that have this formula are Emma (2020) and Persuasion (2022). This research will discuss the ideal romance formula in the movie scripts Emma (2020) and Persuasion (2022) using Radway's ideal romance formula theory and comparative literature theory. The purpose of this study is to find out the differences of the ideal romance formula in the movie scripts of Emma (2020) and Persuasion (2022). This research is qualitative research with a comparative descriptive research method. The results obtained from this research are that Emma fulfills 10 out of 13 functions with the 4th, 5th, and 10th functions which are not fulfilled. Meanwhile, Persuasion also fulfills 10 out of 13 functions with the 3rd, 4th, and 10th functions which are not fulfilled. This is due to the theme of romance which is raised differently. Emma (2020) has the theme from best friends to lover, while Persuasion (2022) has the theme from ex to lover.